1958
DOI: 10.1083/jcb.4.2.219
|View full text |Cite
|
Sign up to set email alerts
|

An Electron Microscopic Study of the Ductuli Efferentes and Rete Testis of the Guinea Pig

Abstract: The ductnii efferentes and rete testis of the guinea pig were isolated by micro dissection, fixed in cold buffered osmium tetroxide, and sectioned for examination with the light and electron microscopes.Proximal and distal segments of the duetnii efferentes were identified and their respective cytological organizations characterized. The cytological components of the rete testis are briefly described and figured.Non-ciliated and dliated ceils are found in both segments of the ductuli efferentes. The non-cillat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

1975
1975
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(23 citation statements)
references
References 16 publications
1
22
0
Order By: Relevance
“…There are, however, some differences in the intracellular structure and content betw-een the non-ciliated cells of the ductuli efferentes proximales and ductuli efferentes distales, as show'll above in the Japanese quail, and in the domestic fowl [unpublished ultrastructural observations]. Ladman and Young [1958] have also shown that there are regional differences in the struc ture of the proximal and distal segments of the ductuli efferentes of the guinea pig.…”
Section: Discussionmentioning
confidence: 87%
“…There are, however, some differences in the intracellular structure and content betw-een the non-ciliated cells of the ductuli efferentes proximales and ductuli efferentes distales, as show'll above in the Japanese quail, and in the domestic fowl [unpublished ultrastructural observations]. Ladman and Young [1958] have also shown that there are regional differences in the struc ture of the proximal and distal segments of the ductuli efferentes of the guinea pig.…”
Section: Discussionmentioning
confidence: 87%
“…Different hypotheses have been suggested to the origin and physiological role of the dark cells. [38] as well as [39] have considered it a modification of a single cell type at different phases of its metabolic cycle. [40][41][42][43][44] believed that, these cells are holocrine secretory cells as they lack stereocilia and have large clear vacuoles with finely granulated material.…”
Section: Discussionmentioning
confidence: 99%
“…The capacity of this epithelium to absorb material from the lumen has been suggested in early studies (van Wagenen, 1925;Wagenseil, 1928;Young, 1933;Mason and Shaver, 1952). More recent electron-microscopic investigations performed with the use of electron-dense markers clearly indicated that the nonciliated epithelial cells readily incorporated these substances (Ladman and Young, 1958;Burgos et al, 1959;Holstein, 1964;Sedar, 1966, Morita, 1966Ladman, 1967;Yokoyama and Chang, 1971;Hrudka, 1980, 1981). Exhibiting numerous pinocytic vesicles, multivesicular bodies, and lysosomes, these epithelial cells appear suitably specialized to be effective endocytic cells (Montorzi and Burgos, 1967;Hoffer, 1972;Hamilton, 1975;Ramos and Dym, 1977;Flickinger et al, 1978;Jones et al, 1979).…”
mentioning
confidence: 88%